Integrating Technology into Extensive Reading Activities for University Students - Settiawan, Dodi (State Islamic University of Sultan Syarif Kasim Riau, 2012)
Extensive reading can be the best way for the students to develop their language competencies. However, most of them do not read in English extensively. They do not read English books, magazines, and other materials once they leave the classroom. The unavailable of reading materials written in English that well within their linguistic competence and low motivation to read impede them to read extensively. That means the instructors have to introduce suitable reading materials to them, motivate and support them to read extensively, and monitor and evaluate their extensive reading activities in order to help themread in English and enjoy it. This article presents an alternative way to the teaching EFL reading that can help university students being readers of English.